Study of thermal insulation materials influence on the performance of thermoelectric generators by creating a significant effective temperature difference. (1st March 2020) - Lv, Song; Liu, Minghou; He, Wei; Li, Xinlong; Gong, Wei; Shen, Sheng
Highlights: Key parameters were evaluated for their impact on the TE module performance. Heat losses in an integration TE module in practical are considered. Thermal insulation materials are filled into TE module to improve its performance. The relevant parameters affecting TE modules' performance have been discussed. Abstract: Thermoelectric generator are attractive heat engines because they can convert heat directly into electricity via Seebeck effect. However, the energy conversion efficiency of today's thermoelectric generators is significantly lower than that of conventional mechanical engines. Materials and devices are the main direction of its improvement. Although thermoelectric material has been making some progress, actual thermoelectric devices has remained stagnant with rather poor efficiencies. In this paper, a mathematical model containing heat losses ignored by previous studies are developed and used to discuss how to reduce heat losses to improved thermoelectric performance. In order to reduce and eliminate the impact of heat loss and study the effects of heat loss, the segmented thermoelectric modules filling with different insulation fillers are built to verify the accuracy of the model. Self-made experimental instruments are developed to study of the effect of reducing module heat loss on thermoelectric conversion performance. The results show that the filling of insulation materials makes contribution to the improvement of thermoelectric performance, the efficiency of aerogel filled module is 8.225% higher than that of unfilled module, and the efficiency of thermoelectric module can be improved up to 9.12% by adding ideal thermal insulation materials. The results also showed that the performance of TE module depends on the thermal conductivity of filling materials and its' filling rate. Those results provided some practical guidelines for the design and improvement of practical thermoelectric modules.